Bewitching - Flinn, Alex. (New York, NY : HarperTeen, 2013)
Tells the story of Kendra, a witch, and the first three-hundred years of her life, including takes on a classic fairy tale, the 1666 plague in Britain, the "Titanic" disaster, and the story of a modern-day, plain stepsister.
Booklist
Horn Book
School Library Journal
Booklist, January 2012
Bulletin (Center for Children's books), March 2012
Horn Book, March 2012
Keywords: Witches -- Juvenile fiction; Witches -- Fiction; Witches -- Fiction